SYSTEM IN FIDUCIARY GOODS ON PERUM PEGADAIAN CABANG PASAR RUMPUT - Ahmad Bayhaqi; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2005)
In this writing, the author wants to create a mortgage system that has computerized goods. Which has a computerized system was created to replace the use of the system is still manually, because if you are still using manually generated a lot of problems in data processing is data - the data is often lost or mixed up. Therefore, a computerized system that already is very well apply to companies that serve many customers. In connection with this writing, the author discusses about mortgaging system of goods and programs using Microsoft Visual Basic 6.0.